2020
DOI: 10.15294/jpii.v9i2.23208
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Gadget-Based Interactive Multimedia in Improving Generation Z’s Scientific Literacy

Abstract: Scientific literacy is very important to generation Z (Gen-Z), while Gen-z’s scientific literacy in Indonesia needs to be improved. The use of gadgets by Gen-Z almost all the time in their daily lives enables research to improve scientific literacy by using gadgets. This study aims to determine the effectiveness of gadget-based interactive multimedia to improve Gen-Z scientific literacy and describe the Gen-Z response to interactive multimedia. This research was a pre-experiment study with one group pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 22 publications
1
51
0
7
Order By: Relevance
“…Maskur et al (2019) revealed that one of the advantages of this model is its ability to encourage students to be active and think optimally to gain knowledge. The 5E learning model activity has a positive effect on student involvement in learning: a) contributes significantly to student learning and interest in learning; b) helps students to develop their scientific process skills; c) is easily applied in science classes (Widodo et al, 2020). Student activeness in this study is driven by integrating 5E learning cycle teaching materials with local wisdom, such as activities involving students exploring, explaining, describing, and evaluating daily problems presented in teaching materials.…”
Section: Figure 1 Critical Thinking Skills Indicatormentioning
confidence: 99%
“…Maskur et al (2019) revealed that one of the advantages of this model is its ability to encourage students to be active and think optimally to gain knowledge. The 5E learning model activity has a positive effect on student involvement in learning: a) contributes significantly to student learning and interest in learning; b) helps students to develop their scientific process skills; c) is easily applied in science classes (Widodo et al, 2020). Student activeness in this study is driven by integrating 5E learning cycle teaching materials with local wisdom, such as activities involving students exploring, explaining, describing, and evaluating daily problems presented in teaching materials.…”
Section: Figure 1 Critical Thinking Skills Indicatormentioning
confidence: 99%
“…Isdaryanti et al (2018) showed that science learning management integrated with character education is very good. Widodo et al (2020) revealed that interactive multimedia was developed effectively to improve students' scientific literacy, but Gen Z students suggested that multimedia enter the device/platform to be accessed anytime. Afriana et al (2016) said that project-based learning integrated with STEM (Science, Technology, Engineering, and Mathematics) could increase scientific literacy more significantly.…”
Section: Fourthmentioning
confidence: 99%
“…Moreover, by having this learning process, students can connect to the network to share and find out new information (Layona et al, 2018;Goodsett, 2020). Then, the learners' beliefs based on new learning will be modified, and be linked to the network to share perceptions and search for new information (Kumari et al, 2020;Widodo et al, 2020). All in all, communication between distance learning and AR-based multimedia can help learners to study in an enjoyable environment.…”
Section: Distance Learning With Augmented Realitybased Multimediamentioning
confidence: 99%
“…Also, every learner needs to master scientific literacy covering its scientific knowledge, scientific process skill, and scientific attitudes (Sinaga et al, 2017). Every learner is also invited on not only mastering this literacy but also improving this since scientific literacy development is vital in facing and solving problems in the daily life (Tuli & Mantri, 2020;Widodo et al, 2020). Scientific literacy is essential because students can contribute and interact in society by having this literacy, also apply the scientific knowledge in making a decision and giving solutions to the problems (Rokhmah et al, 2017;Ratini et al, 2018).…”
Section: Students' Scientific Literacymentioning
confidence: 99%